Analysis the Effectiveness of the Public Accounting Information System in the Sei Sikambing D Sub-District, Medan - Marsaulina Sirait; Galih Supraja; Miftha Rizkina (Universitas Dehasen Bengkulu, 2026)
The purpose of this study is to analyze the effectiveness of the Public Accounting Information System (PAIS) in Sei Sikambing D Sub-District, Medan using the DeLone & McLean Model. This research employs a descriptive qualitative method with data collection techniques through in-depth interviews, observations, and documentation involving three key informants consisting of the Sub-District Head as Budget User Authority (KPA), Assistant Expenditure Treasurer, and Financial Data Management Staff. The analysis was conducted based on six dimensions of information system effectiveness: system quality, information quality, service quality, intensity of use, user satisfaction, and net benefits. The research findings indicate that PAIS through the SIPD application has been effective in producing accurate and timely financial information with near-perfect accuracy rates and 100% reporting timeliness. However, system effectiveness is hampered by server infrastructure instability experiencing disruptions averaging twice per month with durations up to a full day, as well as limited training frequency conducted only once annually. Nevertheless, PAIS provides significant benefits in enhancing transparency through real-time access by central government, strengthening accountability with audit trail features, and improving operational efficiency through reporting process automation. Research implications suggest the need for increased server capacity, training intensification at least twice annually, and development of backup procedures to ensure operational continuity during system disruptions.